2023
DOI: 10.1021/acs.iecr.3c01036
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Drag Reduction by Polymer Additives at High Reynolds Numbers Using Rheological Measurements

Abstract: In industrial applications such as hydraulic water fracking, polymers are added at dilute concentrations to the flow causing significant drag reduction (DR) and leading to a massive reduction to pump energy cost. In recent years, an alternative approach that is based on rotational flow has shown capabilities of measuring DR based purely on rheological testing. Nonetheless, there are some limiting assumptions in this approach that can lead to inaccurate interpretation of the data, especially for non-Newtonian p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…It suggests that the decrease in DR with the addition of salt is a direct consequence of reduction in viscosity. Although a reduction in viscosity can indicate a decrease in DR, other rheological parameters, such as shear stress, should be considered for an accurate quantification of DR …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It suggests that the decrease in DR with the addition of salt is a direct consequence of reduction in viscosity. Although a reduction in viscosity can indicate a decrease in DR, other rheological parameters, such as shear stress, should be considered for an accurate quantification of DR …”
Section: Resultsmentioning
confidence: 99%
“…Once the concentration exceeds c *, the increase in concentration results in retarded DR onset . It should be noted that in cases where the concentration was relatively high, the relation in eq becomes inaccurate as the viscosity of the polymer became an important factor. , For instance, Hashlamoun et al showed that DR has quadratic dependence on the viscosity ratio between the solvent and polymer solutions. This dependence may not be relevant in the flow loop case, where Re is very high, and consequently, the viscosity of the polymer solution can be as low as that of the solvent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From these measurements, the averaged shear stresses (τ) and the shear strain rates (γ̇) are calculated in the stable and unstable regions based on rheometer-related geometrical constants [i.e., stress constant (α) and strain constant (β)]. In our recently published work, a double-gap concentric cylinder [HR-20 rheometer (TA Instruments–Waters LLC, DE, USA)] was used for such measurements. The setup consists of a Peltier jacket and an air-cooled Peltier circulator used to control the temperature.…”
Section: System Used For Drag Reduction Measurementsmentioning
confidence: 99%